Morphology and molecular orientation of ethyl-substituted dicyanovinyl-sexithiophene films for photovoltaic applications - Hinrichs, K; Levichkova, M; Wynands, D; Wynands, D; Walzer, K; Eichhorn, K; Bäuerle, P; Leo, K; Riede, M (Elsevier, 2012)
Enhancement of the efficiency of organic solar cell devices requires knowledge about the structure of the organic layers involved. Films of the donor material dicyanovinyl-sexithiophene bearing four ethyl side-chains at thiophenes two and five DCV6T-Et(2,2,5,5) (DCV6T-Et) are prepared by thermal evaporation in high vacuum at various thicknesses and substrate temperatures. Infrared spectroscopic ellipsometry is used for determination of the molecular orientation in the thin films grown on room temperature (RT) substrate. From simulation of the IR ellipsometric data, the film thickness and the anisotropic optical constants of the DCV6T-Et films are determined. It is found that the optical constants strongly depend on the film thickness. Different average molecular orientations are determined for a few molecules thin (4 nm) and somewhat thicker (20 nm) films. Furthermore, the evolution of the surface morphology of films deposited at elevated substrate temperatures (80°C, 100°C) is studied in comparison to the thick RT-film. Atomic force microscopy images indicate that the growth on heated substrate is accompanied by an increase in grain size and surface roughness of the films. Simultaneously, the measured optical absorption spectra display structured and increased absorption in the red spectral region for the DCV6T-Et films deposited at higher substrate temperatures. The changes in surface topography and optical response relate to improved molecular arrangement induced by the substrate heating. To demonstrate the morphological influence on solar cell performance, we finally discuss DCV6T-Et/C60 planar heterojunction solar cells composed of DCV6T-Et films deposited at different substrate temperatures. © 2012 Elsevier B.V.